Diseminasi Pemanfaatan Animaker sebagai Media Pembelajaran Interaktif bagi Generasi Alpha di SDN Wadas IV Karawang - Nurhasan; Yadi Fahmi Arifudin; Agus Susanto; Defi Tri Mulyani; Ilham Tafriji; Shinta Diana (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service aims to describe the process of dissemination and utilization of Animaker as an interactive learning media for the Alpha generation at SDN Wadas IV Karawang, as well as its impact on teacher competency and learning quality. The activity was carried out through a series of lectures, discussions, and practices involving 18 elementary school teachers in a workshop on the use of Animaker. Primary data were obtained from observations, pretest-posttest, discussion notes, and Animaker media products produced by teachers, while secondary data came from school documents and literature related to digital media and the Alpha generation. Descriptive analysis showed an increase in the average score of teachers from 72.77 (pretest) to 77.77 (posttest), which indicates a strengthening of teachers' knowledge and skills in designing and integrating animated visual media in learning. Teachers experienced a change in perception, from viewing animation as mere entertainment to a strategic pedagogical medium to bridge abstract concepts and learning characteristics of the Alpha generation. This study also identified the main obstacles in the aspects of ICT facilities, internet stability, and time constraints, while formulating strengthening strategies in the form of tiered training, a community of practitioners, and school policy support so that the implementation of Animaker is sustainable and can be replicated in other elementary schools.